Return to Learn: A review of cognitive rest versus rehabilitation after sports concussion. - Eastman, Amelia; Chang, Douglas G. (NeuroRehabilitation, 2015)
BACKGROUND: Cognitive rest is the recommendation for all patients with acute sports concussion. OBJECTIVE/METHODS: A comprehensive literature search was conducted for the research question "What is the optimal cognitive load for patients with a sports concussion?" RESULTS: Seven studies met the inclusion criteria. The optimal cognitive load for patients after sports concussion is yet to be determined. CONCLUSIONS: Additional controlled trials of cognitive rehabilitation are needed to establish best clinical practice. The authors suggest memory training, cognitive behavioral therapy, and environmental interventions as areas of future research for sports concussion injuries.